Dynamics of Formil Legal Procedures Establishment of Laws and Regulations - Kaharuddin, Kaharuddin; Zaifa, Gilang Abi; Dirkareshza, Rianda (Constitutionale, 2023)
As a state of law, Indonesia certainly cannot be separated from legal policies in terms of drafting laws and regulations. The definition of legal policy is legal policy as a means and procedure that can be used by the government to build a legal system. Based on this, a problem formulation is drawn, namely about how the political pattern of legislation in the Job Creation Law and how the development and participation of the community in making the Job Creation Law. The research method used is normative research, and the approach used is a statutory and conceptual approach. The result of the discussion is that the political pattern determines the purpose of what will be compiled in laws and regulations. In Indonesia, its formation must be based on Pancasila where Pancasila is the fundamental norm of the state. The development of an increasingly critical and wise society must certainly receive attention in order to be involved in the formation of laws and regulations. Community involvement here aims to later the rules formed can be useful for the community.